The Business Cycles in the Philippines: A Characterization - Leitner, Sandra M. (Philippine Management Review; Vol 12 (2005), 2010)
This paper provides an overall characterization of the Philippine business cycles covering the period 1981 to 2003 in terms of volatility, co-movement and persistence. The period under investigation brought about three cycles: 1983-1989, 1989-1997 and 1997-2000 with initially very erratic but over time smoother fluctuations. In resemblance with industrialized economies, investment turns out to be the most volatile and consumption the least volatile national expenditure component, potentially pointing at Keynes' assertion of "animal spirits" of investors as the source for the former phenomenon. Further, with the exception of prices, inflation and the terms of trade, all variables have strong and positive correlations with GDP. The strong negative price-output correlation and the weak positive inflation-output correlation identify supply shocks as the triggering factor for observed business cycles, pointing at either technological change or drastic changes in the weather as possible spurring factors. Moreover, the investigation clearly reveals procyclical fiscal and monetary policy interventions, contradicting theoretical prescriptions of countercyclical stabilization policies to swiftly overcome economic recessions. Finally, all key macroeconomic variables show fairly low persistence, substantiating the Philippines' popularity for its boom-bust cycles.